2022
DOI: 10.1136/jech-2022-219074
|View full text |Cite
|
Sign up to set email alerts
|

Peptic ulcer as mediator of the association between risk of gastric cancer and socioeconomic status, tobacco smoking, alcohol drinking and salt intake

Abstract: BackgroundPeptic ulcer disease (PUD) and gastric cancer (GC) are more prevalent in individuals with low socioeconomic status (SES) and share several risk factors. The aim of this study was to investigate the mediating role of PUD in the association between established risk factors and GC.MethodsWe conducted a pooled analysis of 12 studies from the Stomach Cancer Pooling Project Consortium, including a total of 4877 GC cases and 11 808 controls. We explored the mediating role of PUD in the association between S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In addition to commonality in risk factors, PUD is shown to mediate the carcinogenic impact of some of the established GC risk factors. Previous study by the SToP consortium revealed the mediation role for PUD and a number of risk factors in development of GC [37]. The PUD was responsible for mediating 36% of the effect of tobacco smoking on gastric carcinogenesis [37].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to commonality in risk factors, PUD is shown to mediate the carcinogenic impact of some of the established GC risk factors. Previous study by the SToP consortium revealed the mediation role for PUD and a number of risk factors in development of GC [37]. The PUD was responsible for mediating 36% of the effect of tobacco smoking on gastric carcinogenesis [37].…”
Section: Discussionmentioning
confidence: 96%
“…Previous study by the SToP consortium revealed the mediation role for PUD and a number of risk factors in development of GC [37]. The PUD was responsible for mediating 36% of the effect of tobacco smoking on gastric carcinogenesis [37].…”
Section: Discussionmentioning
confidence: 96%
“…It is worthy of note that in the subgroup analysis of upper GI perforation, smoking history was indicated to be associated with prognosis. Smoking is a known risk factor for GI ulcers; previous studies have established a link between smoking and peptic ulcers ( 34 , 35 ). A study performed by Jha et al ( 36 ) suggested that smoking accounts for almost half of all male mortality in the lowest social strata of various countries.…”
Section: Discussionmentioning
confidence: 99%
“…Through a comprehensive literature search on various databases (PubMed/ MEDLINE, Embase, Institute for Scientific Information Web of Science, and the Cochrane Database of Systematic Reviews), we identified all meta-analyses, pooled analyses, and reviews on the association between cigarette smoking and cancer risk published up to October 12 2022. In particular, we identified 20 systematic reviews/metaanalyses [8][9][10][11][12][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and 16 pooled analyses [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] on GC (Supplementary Fig. 1).…”
Section: Search Strategymentioning
confidence: 99%